Rationale and design of the TACTICS registry: Optical coherence tomography guided primary percutaneous coronary intervention for patients with acute coronary syndrome. Issue 6 (December 2022) - Yamamoto, Myong Hwa; Kondo, Seita; Mizukami, Takuya; Yasuhara, Sakiko; Wakabayashi, Kohei; Kobayashi, Nobuaki; Sambe, Takehiko; Hibi, Kiyoshi; Nanasato, Mamoru; Sugiyama, Tomoyo; Kakuta, Tsunekazu; Kondo, Takeshi; et al.
Abstract: Background: Recent retrospective investigations have suggested that optical coherence tomography (OCT) enables the diagnosis of underlying acute coronary syndrome (ACS) causes such as plaque rupture, plaque erosion, and calcified nodule. The relationships of these etiologies with clinical outcomes, and the clinical utility of OCT-guided primary percutaneous coronary intervention (PCI) are not systematically studied in real-world ACS treatment settings. Methods: The TACTICS registry is an investigator-initiated, prospective, multicenter, observational study to be conducted at 21 hospitals in Japan. A total of 700 patients with ACS (symptom onset within 24 h) undergoing OCT-guided primary PCI will be enrolled. The primary endpoint of the study is to identify the underlying causes of ACS using OCT-defined morphological assessment of the culprit lesion. The key secondary clinical endpoints are hazard ratios of the composite of cardiovascular death, non-fatal myocardial infarction, heart failure, or ischemia-driven revascularization in patients with underlying etiologies at the 12- and 24-month follow-ups. The feasibility of OCT-guided primary PCI for ACS will be assessed by the achievement rates of optimal post-procedural results and safety endpoints. Conclusion: The TACTICS registry will provide an overview of the underlying causes of ACS using OCT, and will reveal any difference in clinical outcomes depending on the underlying causes. The registry will also inform on the feasibility of OCT-guided primary PCI for patients with ACS. Graphical abstract: The TACTICS (Tokyo, Kanagawa, Chiba, Shizuoka, and Ibaraki active OCT applications for ACS) registry. ACS, acute coronary syndrome; OCT, optical coherence tomography; PCI, percutaneous coronary intervention. Unlabelled Image Highlights: TACTICS is an investigator-initiated prospective multicenter observational study. Optical coherence tomography (OCT)-guided primary percutaneous coronary intervention (PCI) will be performed. The primary endpoint is to identify the underlying causes of acute coronary syndrome (ACS). Clinical outcomes and feasibility of OCT-guided PCI will be clarified.